Primitive Polynesian Economy. - Firth, Raymond (Taylor and Francis, 2013)
A great classic of British anthropology, Primitive Polynesian Economy is structured as follows: · Problems of Primitive Economics · Food and Population in Tikopia · Knowledge, Technique and Economic Lore · The Labour Situation · Ritual in Productive Activity · Economic Functions of the Chiefs · Property and Capital in Production · Principles of Distribution and Payment · Exchange and Value · Characteristics of a Primitive Economy First published in 1939.